The Effect of Leadership, Competence, and Organizational Culture on Islamic Motivation and Employee Performance at PT Sumber Swarna Pratama, North Morowali Regency, and PT Trio Kencana, Parigi Moutong Regency, Central Sulawesi - ., Surianto; Ramli, Mansyur; Zakaria, Junaidin; Selong, Abbas (Journal of Cultural Analysis and Social Change, 2026)
This study examines the effect of leadership, competence, and organizational culture on Islamic motivation and employee performance at PT Sumber Swarna Pratama, North Morowali Regency, and PT Trio Kencana, Parigi Moutong Regency, Central Sulawesi. Using a quantitative explanatory approach with a cross-sectional survey design, data were collected through structured questionnaires from 222 employees selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) after passing validity, reliability, and classical assumption tests. The results reveal that leadership and competence have a positive and significant effect on employee performance, while organizational culture does not show a significant direct effect on performance. Furthermore, leadership, competence, and organizational culture each have a positive and significant effect on Islamic motivation. Islamic motivation, in turn, has a strong positive and significant effect on employee performance, indicating its important mediating role in strengthening the relationship between leadership, competence, organizational culture, and performance. These findings suggest that improving leadership quality, enhancing employee competence, and fostering a value-based organizational culture that supports Islamic motivation are strategic approaches for achieving sustainable improvements in employee performance within mining organizations operating in a predominantly Muslim context.